Analisis Pemilihan Pemasok Kelapa Sawit yang Berkelanjutan dengan Menggunakan Metode PROMETHEE (Studi Kasus pada PT Perkebunan Nusantara III) - Fatma Saqdiah; Heti Mulyati; Alim Setiawan Slamet (IPB University, 2022)
Suppliers are one of the business partners who play an important role in ensuring the availability of raw materials needed in production activities in a company. Companies in meeting the needs of raw materials in production activities of course conduct a selection of suppliers who can meet the supply of quality raw materials and on time in the delivery of goods. The purpose of this study is to develop a method of assessing the performance of palm oil suppliers that does not only look at economic criteria but also pays attention to sustainability factors, namely economic, social and environmental criteria in choosing the best supplier. The supplier performance assessment method aims to obtain the priority of the selected supplier by using the Multi Criteria Decision Making-PROMETHEE method. Assessment of supplier selection is carried out by filling out a questionnaire by two expert respondents, namely the Chief Engineer and Quality Assurance Assistant. This case study of sustainable supplier performance assessment was conducted in one of the state-owned companies engaged in plantation commodities, namely PT Perkebunan Nusantara III. Based on the type of decision-making using the PROMETHEE method, the suppliers selected and meeting the supplier performance assessment with sustainability criteria were UD. Satya Radja and UD. Meji Jaya suppliers with the highest Net Flow value of 0,1250.